Nobody likes a goblin - Hatke, Ben (First Second, 2016)
Goblin, a cheerful little homebody, lives in a cosy, rat-infested dungeon, with his only friend, Skeleton. Every day, Goblin and Skeleton play with the treasure in their dungeon. But one day, a gang of "heroic" adventurers bursts in. These marauders trash the place, steal all the treasure, and make off with Skeleton-leaving Goblin all alone! It's up to Goblin to save the day. But first he's going to have to leave the dungeon and find out how the rest of the world feels about goblins."--Amazon.com.